Antimicrobial Activity and Some Physiochemical Properties of Pumpkin (Cucurbita pepo L.) Seed oil - Abdel-Rahim, Awad A.; A.Osman, Shomoos; A. A. Yasin, Atif; Abdelraheem, Yasir M. (Gezira Journal of Engineering and Applied Sciences, 2018)
Pumpkin and squash plants grow in warm, humid regions,  cannot withstand frost. Most of the pumpkin consumed in Sudan was grown in Kordufan (western sudan).The use of plants and their extracts as remedies for curing many diseases have stimulate studies for investigating the presence of effective antimicrobial substances in them The present study was investigating the physiochemical and the biological activity of the different solvent extracts of pumpkin ( Cucurbita pepo ) seed oil (hexane, ethanol, methanol, and water) against two fungi  ( A. niger and P. italicum ) and two bacteria (E.coli and Staph. aureus). The inhibition zone method  was used for bacterial tests and the mycelia weight method was used for the fungal study. The results of the physiochemical showed that the specific gravity of the oil was between 0.997–0.908. The Refractive index was between 1.46–1.470. The average iodine value was 117.97,  the free fatty acids was between 0.2 and 0.55. The peroxide value was in the normal range (5.92–9 and the average saponification value was about 188. The biological study showed that the fresh and the dry weights of mycelia were highly reduced, although the reduction was only statistically different at the higher concentrations (75-100%).The fresh weights for the higher concentrations were 1.65 and 1.0 and for the lower concentrations were 3.1 and 3.7 for both A. niger and P. italicum , respectively. The inhibition zone of growth of both bacteria was far greater than that of the control treatment. The results indicated that the pumpkin oil extracts are more effective against bacteria compared to fungi. The hexane extract  was giving a large  inhibition zone (about 26.5 mm diameter) while, the ethanol extract was giving a less inhibition zone (about 14.2.mm diameter). On the other hand both methanol and the aqueous extracts were giving very low inhibition zones (13.5 and 13.6 mm diameter, respectively). However, more physiochemical characterizations need to be done  and the antifungal and the antibacterial properties  should verified in any further  studies on the pumpkin seed oil.